Circulating factors associated with sarcopenia during ageing and after intensive lifestyle intervention. Issue 3 (10th April 2019) - Li, Chun‐wei; Yu, Kang; Shyh‐Chang, Ng; Li, Guo‐xun; Jiang, Ling‐juan; Yu, Song‐lin; Xu, Long‐yu; Liu, Rong‐ji; Guo, Zi‐jian; Xie, Hai‐yan; Li, Rong‐rong; Ying, Jie; et al.
Abstract: Background: Ageing, chronic diseases, prolonged inactivity, and inadequate nutrition pose a severe threat to skeletal muscle health and function. To date, experimental evidence suggests that ageing‐related subclinical inflammation could be an important causative factor in sarcopenia. Although inflammatory signalling has been implicated in the pathogenesis of experimental animal models of sarcopenia, few studies have surveyed the clinical association between circulating factors and muscle mass in patients before and after lifestyle interventions. In this study, we evaluated whether proinflammatory cytokines are associated with the onset of sarcopenia, which circulating factors are associated with the severity of sarcopenia, and how these factors change after lifestyle interventions in sarcopenic elderly persons. Methods: A total of 56 elderly subjects (age ≥ 60 years) with sarcopenia and 56 elderly non‐sarcopenic subjects, who met entry criteria and had given informed consent, were selected from the Peking Union Medical College Hospital multicentre prospective longitudinal sarcopenia study for testing relevant circulating factors. Thirty‐two elderly subjects from the sarcopenic cohort completed a 12 week intensive lifestyle intervention programme with whey supplements (30 g/day) and a personalized resistance training regimen. The levels of proinflammatory cytokines and metabolic hormones, pre‐intensive and post‐intensive lifestyle interventions, were measured. Results: The sarcopenic group was significantly older (72.05 ± 6.54 years; P  < 0.001), more likely to be inactive and female (57.1% of all sarcopenic patients), and had a higher prevalence of type 2 diabetes (16% higher risk). Compared with non‐sarcopenic subjects, serum interleukin (IL)‐6, IL‐18, tumour necrosis factor‐α (TNF‐α), TNF‐like weak inducer of apoptosis (TWEAK), and leptin were significantly higher, while insulin growth factor 1, insulin, and adiponectin were significantly lower in sarcopenic patients (all P  < 0.05). Logistic regression analyses revealed that high levels of TNF‐α (>11.15 pg/mL) and TWEAK (>1276.48 pg/mL) were associated with a 7.6‐fold and 14.3‐fold increased risk of sarcopenia, respectively. After adjustment for confounding variables, high levels of TWEAK were still associated with a 13.4‐fold increased risk of sarcopenia. Intensive lifestyle interventions led to significant improvements in sarcopenic patients' muscle mass and serum profiles of TWEAK, TNF‐α, IL‐18, insulin, and adiponectin (all P  < 0.05). Conclusions: High levels of the inflammatory cytokines TWEAK and TNF‐α are associated with an increased risk of sarcopenia, while the metabolic hormones insulin growth factor 1, insulin, and adiponectin are associated with a decreased risk of sarcopenia in our Chinese patient cohort. Intensive lifestyle interventions could significantly improve muscle mass, reduce inflammation, and restore metabolic hormone levels in sarcopenic patients. This trial was registered at clinicaltrials.gov as NCT02873676.